Communicating the bond between Law and Literature: Human Rights Issues in Select English Poems - Singh, Alka (LinguaEducare: Journal of English and Linguistic Studies, 2025)
The present research paper aims to examine and explore human rights issues in Sarojini Naidu’s ‘The Broken Wing’, Elizabeth Barrett Browning’s ‘The Cry of the Children’ and Langston Hughes’ ‘The Negro Speaks of Rivers’. These verses span diverse historical, cultural, and political landscapes. Poetry has long served as a powerful medium for articulating the human condition, voicing dissent, and advocating for justice. Each poem is highly evocative and deeply rooted in its socio-political context, revealing the poet’s deep engagement with themes such as freedom, oppression, and the resilience of human spirit. Naidu’s ‘The Broken Wing’ reflects the colonial and nationalistic struggles of early 20th-century India, portraying the yearning for liberation and spiritual dignity, and reflects India’s spiritual resilience of a colonized people. Browning’s ‘The Cry of the Children’ is a searing indictment of child labour in Victorian England, highlighting the moral failure of industrial society. Hughes’s ‘The Negro Speaks of Rivers’ delves into African American identity and historical memory, emphasizing continuity, heritage, and endurance in the face of racial injustice. Through these texts, the poets not only document suffering but also inspire resistance and hope, making poetry a vital space for human rights discourse.